Чернігівське видання «Акафісты с каноны» 1785 р. - Ситий, І. (Сiверянський лiтопис, 2012)
Стаття присвячена виданню друкарнею Чернігівського Троїцько-Іллінського монастиря книги «Акафісты с каноны». Статья посвящена изданию типографией Черниговского Троицко-Ільинского монастиря книги «Акафісты с каноны». The article describes the activity of Chernigiv Illinska typography in the of the 18 century. The attachment contains the documents, which throw light upon the process of preparation and printing in Chernigiv in 1785 of the worc «Acafisty s canony».